Evolving Differentiation in African Trypanosomes - Quintana, Juan F; Zoltner, Martin; Field, Mark C (Trends in parasitology, 2021)
Differentiation is a central aspect of the parasite life cycle and encompasses adaptation to both host and environment. If we accept that evolution cannot anticipate an organism's needs as it enters a new environment, how do parasite differentiation pathways arise? The transition between vertebrate and insect stage African trypanosomes is probably one of the better studied and involves a cell-cycle arrested or 'stumpy' form that activates metabolic pathways advantageous to the parasite in the insect host. However, a range of stimuli and stress conditions can trigger similar changes, leading to formation of stumpy-like cellular states. We propose that the origin and optimisation of this differentiation program represents repurposing of a generic stress response to gain considerable gain-of-fitness associated with parasite transmission.
Keywords: fyziologický stres; Stress, Physiological; stadia vývoje; buněčný cyklus; Trypanosoma; Life Cycle Stages; biologická evoluce; Biological Evolution; Cell Cycle